The Highland Health Advocates: a preliminary evaluation of a novel programme addressing the social needs of emergency department patients. Issue 9 (22nd June 2017) - Losonczy, Lia Ilona; Hsieh, Dennis; Wang, Michael; Hahn, Christopher; Trivedi, Tarak; Rodriguez, Marcela; Fahimi, Jahan; Alter, Harrison
Abstract : Objectives: Patients commonly come to the emergency department (ED) with social needs. To address this, we created the Highland Health Advocates (HHA), an ED-based help desk and medical-legal partnership using undergraduate volunteers to help patients navigate public resources and provide onsite legal and social work referrals. We were able to provide these services in English and Spanish. We aimed to determine the social needs of the patients who presented to our ED and the potential impact of the programme in resolving those needs and connecting them to a 'medical home' (defined as a consistent, primary source of medical care such as a primary care doctor or clinic). Methods: ED patients at a US safety net hospital were enrolled in a 1:2 ratio in a quasi-experiment comparing those who received intervention from the HHA during a limited access rollout with controls who received usual care on days with no help desk. We collected a baseline social needs evaluation, with follow-up assessments at 1 and 6 months. Primary outcomes were linkages for the primary identified need and to a medical home within 1 month. Other outcomes at 6 months included whether a patient (1) felt helped; 2) had a decreased number of ED visits; (3) had the primary identified need met; (4) had a primary doctor; and (5) had a change in self-reported health status. Results: We enrolled 459 subjects (intervention=154, control=305). Housing (41%), employment (23%) and inability to pay bills (22%) were participants' top identified needs. At baseline, 32% reported the ED as their medical home, with the intervention cohort having higher ED utilisation (>1 ED visit in the prior month: 49% vs 24%). At 1 month, 185 (40%) subjects were reached for follow-up, with more HHA subjects linked to a resource (59% vs 37%) and a medical home (92% vs 76%). At 6 months, 75% of subjects felt HHA was helpful and more subjects in the HHA group had a doctor (93% v 69%). No difference was found in ED utilisation, primary need resolution or self-reported health status. Conclusions: Health-related social needs are common in this US safety net ED. Our help desk is one possible model for addressing social needs.